Aplikasi Pupuk Daun Gandasil D Terhadap Pertumbuhan Bibit Jabon Merah (Anthocephalus macrophyllus Havil) - Telji Y. Palemba1,; Marthen T. Lasut; Josephus I. Kalangi; Alfunsius Thomas (Universitas Sam Ratulangi, 2013)
ABSTRACTFertilization on red Jabon (Anthocephalus macrophyllus Havil) seedling is necessary to accelerate growth and improve the quality of red Jabon.Seedling quality can be seen from the high growth of seedlings, large stem diameter and number of leaves are many. fertilizer that can be used is fertilizer leaf Gandasil D. Fertilizing through the leaves have some advantages, quickly and easily absorbed by the plant and contains macro and micro nutrients to support the growth of the phase vegetative good. This study aimed to determine the effect of foliar fertilizers on the growth of seedlings Gandasil D Jabon red. The results of statistical tests that have been conducted, obtained with leaf fertilizer concentration of 2 grams / liter of water can provide a good vegetative growth in seedlings of red jabon.Key words : red jabon seedling (Anthocephalus macrophyllus Havil), fertilizer leaf Gandasil D.